Warming up with an ice vest: Core body temperature before and after cross-country racing - Hunter, I.; Hopkins, J. T.; Casa, D. J. (Journal of Athletic Training, 2006)
Context: Athletes running in a hot, humid environment may have an increased risk of heat illness. In the 2004 Olympic Games, American and Australian athletes were provided with ice vests designed to cool their bodies before performance. The vest appeared to be effective in keeping body temperatures down and improving the performance of the marathoners. However, body temperatures have not been reported when the vest was used before an actual competition.